2020
DOI: 10.3390/jmse8030200
|View full text |Cite
|
Sign up to set email alerts
|

Towards Marine Dual Fuel Engines Digital Twins—Integrated Modelling of Thermodynamic Processes and Control System Functions

Abstract: This study aims at developing an integrated model that combines detailed engine thermodynamic modelling and the control system functional modelling paving the way towards the development of high-fidelity digital twins. To sufficiently represent the combustion process, a multi-Wiebe function approach was employed, whereas a database for storing the combustion model parameters was developed. The developed model was employed for the systematic investigation of a marine four-stroke dual fuel engine response during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…The proposed framework relied on a digital twin of the engine or on novelty detection algorithms, which were compared against state-of-the-art fully supervised approaches. Utilising data from the validated simulation model of Stoumpos et al (2020), the authors demonstrated that their approach can overcome the problematic requirement for a large amount of labelled samples, that are rarely available, with a decrease in performance of less than 1% compared to state-of-the-art fully-supervised approaches.…”
Section: Ddmsmentioning
confidence: 99%
“…The proposed framework relied on a digital twin of the engine or on novelty detection algorithms, which were compared against state-of-the-art fully supervised approaches. Utilising data from the validated simulation model of Stoumpos et al (2020), the authors demonstrated that their approach can overcome the problematic requirement for a large amount of labelled samples, that are rarely available, with a decrease in performance of less than 1% compared to state-of-the-art fully-supervised approaches.…”
Section: Ddmsmentioning
confidence: 99%
“…This study was based on a modified version of an existing engine thermodynamic model developed for simulating the engine steady state and transient operations in the GT-ISE software [51,52]. In addition, a combinatorial method that employs the nondominated sorting genetic algorithm NSGA III optimisation genetic algorithm along with a fully factorial design of experiments was developed and employed to achieve this study aim.…”
Section: Research Aimmentioning
confidence: 99%
“…The engine model employed in this study is of the zero/one-dimensional (0D/1D) type and was realised in the GT-ISE (v. 2019, Gamma Technologies, Westmont, Illinois, USA) [58], as this software offers the tools and functionalities to enable the effective engine modelling. The engine model of the investigated engine, without considering the EGR and ABP systems, was previously developed for steady state conditions, as described in [51], and transient conditions, as reported in [52]. The detailed description of the model is reported in the previous publications of the authors [51,52] and therefore, it will not repeated herein.…”
Section: Engine Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…All these techniques, which are actually very effective, currently have the limit of providing for the offline processing of the data obtained in the monitoring and subsequent adjustment of the engine. However, numerous studies [8][9][10][11][12] have demonstrated the possibility of simulating engine operation with remarkable precision.…”
Section: Introductionmentioning
confidence: 99%